A qualitative analysis of the networks of tourism SMEs in Germany: managing business networks for knowledge transfer - Braun, Christine (2015)
Theoretically, it is said that social capital encourages individuals and entrepreneurs to engage in business networks. Social capital is the sum of the resource benefits an organisation derives from its network of relationships. These external knowledge sources are particularly relevant for small and medium-sized enterprises (SMEs) because of their lack of internal knowledge stock. Yet, social capital theories have primarily been investigated from a structural perspective to measure benefits through centrality and position in structural holes. To understand the resource benefits, however, it is first necessary to understand what knowledge is available, second the content of the relationship, and third the context and conditions that influence these inter-organisational knowledge transfer relationships. Thus, in this thesis, a relational approach is adopted to generate knowledge on inter-firm relationships at the SME level in order to explore how tourism business networks are operated and managed in such a way that enables the knowledge transfer. This study looks into the business networks in which the SMEs of the tourism industry engage, explains the meaning they ascribe to the knowledge transfer potential among these networks, how they exploit the networks, what knowledge is made available, and the managerial as well as contextual factors that influence the network operation and management.